Assessment of The Mechanical Engineering Programs by Exit Surveys at Universiti Malaysia Pahang - M. S. M., Sani; M. M., Noor; M. R. M., Rejab; A. S., Sulaiman (2008)
This paper focused on the assessment and continuous program improvement of mechanical engineering programs at Universiti Malaysia Pahang. Continuous program improvement is an important factor in ensuring the high quality of the graduates of the engineering programs. Rapid changes in the job market demands have made it vital for the engineering educators to adopt a strategy of continuous quality improvement (CQI) of their academic programs. The faculty of Mechanical Engineering, Universiti Malaysia Pahang is using exit surveys as a tool to explore the assessment of the graduating students of the engineering education. The survey covers the program outcomes (PO’s) elements which have been developed for mechanical engineering program. The objective of this paper to present the outcomes of this assessment processes and discusses how it can be help to improve the mechanical engineering program. The survey was conducted during last academic semester (first semester of the year 2007/2008).